1986
DOI: 10.1128/iai.54.3.751-760.1986
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response of swine to outer membrane components of Haemophilus pleuropneumoniae during infection

Abstract: Sera from pigs infected with Haemophilus (Actinobacilus) pkuropneumoniae were tested for antibodies to outer membrane proteins (OMPs) of the organism by immunoblotting. Convalescent sera were produced in naturally born, colostrum-fed pigs and in cesarean-derived, colostrum-deprived pigs given H. pleuropneumoniae serotype 5 intranasally twice at 5-week intervals. Sera, collected at weekly intervals, were reacted with Sarkosyl-insoluble, OMP-enriched preparations of H. pleuropneumonwe which had been separated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…Our present results were also close to those achieved with SDS-PAGE and itnmunoblotting of OMP frotn Haemophilus pleuropneumoniae (12,25). Pohl et al (19) and Maclnnes & Rosendahl (12) found that H. pleuropneumoniae shared greater homology with members of genus Aetinobaeillus based on phenotypic and deoxyribonucleie acid relatedness than with metnbers of genus Haemophilus.…”
Section: Discussionsupporting
confidence: 89%
“…Our present results were also close to those achieved with SDS-PAGE and itnmunoblotting of OMP frotn Haemophilus pleuropneumoniae (12,25). Pohl et al (19) and Maclnnes & Rosendahl (12) found that H. pleuropneumoniae shared greater homology with members of genus Aetinobaeillus based on phenotypic and deoxyribonucleie acid relatedness than with metnbers of genus Haemophilus.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, treatment of CF with NaIO R , known to oxidize sugar residues to aldehydes, did not abrogate recognition by the mAb, showing that no glycidic substituent was involved in mAb-antigen binding [17]. This treatment only abolished recognition by mAb WB8A11, indicating that at least one of the antigens, the 82-kDa protein, is glycosylated (Fig.…”
Section: Chemical Nature Of the Antigens Recognized By Mabsmentioning
confidence: 91%
“…Samples of BCG CF (15 Wg) were diluted in 100 Wl PBS containing 1 mg ml 3I trypsin or 1 mg ml 3I papain and incubated at 37³C for 2 h. To determine if the epitopes reacting with the mAbs were glycidic, 15 Wg of BCG CF were diluted in 100 Wl of 100 mM Na-acetate pH 4.5, 10 mM NaIO R and incubated at 37³C for 2 h. They were then subjected to SDS-PAGE and abrogation of recognition by the mAbs was evaluated by Western blotting [17].…”
Section: Determination Of the Chemical Nature Of The Antigens And Epimentioning
confidence: 99%
“…1986a,b). Analysis of the serological response to outer-membrane antigens during A. pieuropneumoniae infection in pigs has identified a number of outer-membrane proteins that are only reactive with convalescent serum (Rapp and Ross, 1986), including 76kD and 95 kD iron-repressible proteins (Deneer and Potter, 1989). Reactivity of the sera with outer-membrane proteins from other serotypes and removal of reactive antibody by adsorption with intact cells implicate the existence of conserved surface epitopes.…”
Section: Introductionmentioning
confidence: 99%